1975
DOI: 10.1111/j.1550-7408.1975.tb00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cell Volume of Didinium nasutum During Population Increase*

Abstract: SYNOPSIS. In 3 species of carnivorous protozoa, the rate of individual food intake per generation declines with an increase in the density of the population. In all, the rate of division remains constant. Three hypotheses may be proposed to explain these phenomena: the individual size decreases, thus bringing about a decline in food need; the individuals in the earlier stages of population growth consume excess food which is passed on to later generations to supplement their food intake ; an increase in densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…C. striatum shows logistic growth in the absence of D. nasutum, and has never been observed to drive its bacterial prey extinct (Morin & Lawler 1995). We therefore treat D. nasutum and C. striatum as a simple predator and prey system as previous authors have done with D. nasutum and Paramecium (Gause 1934;Luckinbill 1973Luckinbill , 1974Luckinbill , 1979Salt 1974Salt , 1975Luckinbill & Fenton 1978;Maly 1978;Hewett 1980Hewett , 1987.…”
Section: Methodsmentioning
confidence: 96%
“…C. striatum shows logistic growth in the absence of D. nasutum, and has never been observed to drive its bacterial prey extinct (Morin & Lawler 1995). We therefore treat D. nasutum and C. striatum as a simple predator and prey system as previous authors have done with D. nasutum and Paramecium (Gause 1934;Luckinbill 1973Luckinbill , 1974Luckinbill , 1979Salt 1974Salt , 1975Luckinbill & Fenton 1978;Maly 1978;Hewett 1980Hewett , 1987.…”
Section: Methodsmentioning
confidence: 96%
“…The small size of monoxenic stationary phase cells supports the hypothesis that starvation is the cause of cessation of cell division. Certainly, small size in stationary phase (or as a response to depletion of food) is the usual pattern observed (Dewey and Kidder 1940;Hamilton and Preslan 1969 ;Salt 1975;Taylor and Berger 1976a), and is the predicted situation in the cell growth model proposed by Williams (1967Williams ( , 1971, which approximates the behaviour of a wide variety of cell types. Exponential-phase Tetrahymena transferred from proteose peptone into a non-nutrient medium decrease in size and have a cellular density distinct from stationary-phase cells, as determined by equilibrium density gradient centrifugation (Bruns 1973).…”
Section: Discussionmentioning
confidence: 82%
“…We would expect predator size to be greatest during predator increase, because then prey consumed per predator is high, mean age is high, and starvation is minimal. Mean predator size shows marked cyclical changes in D. nasutum when fed on C. striatum (M. Holyoak, personal observation), or P. aurelia (Salt 1975, Hewett 1988). An unreplicated experiment (M. Holyoak, personal observation) suggested that mean predator volume peaked at approximately two days after predator introduction, which accords with the changes in individual state variables in Fig.…”
Section: Discussionmentioning
confidence: 99%